Polypropylene/graphene nanoplatelets nanocomposites with high conductivity via solid-state shear mixing - Zhao Xiaoliang (De Gruyter, 2021)
Polypropylene/GNP nanocomposites with enhanced antistatic performance, impact strength, and thermostability via solid-state shear mixing processed.